Application of 3D navigation for osteotomy of DDH in children: A systematic review and meta-analysis - Liu, Yunlong; Yang, Yancai; Ding, Sheng (Frontiers in Pediatrics, 2022)
Objective To systematically review the current articles to compare the efficacy and safety of 3D navigation-assisted osteotomy of DDH with conventional osteotomy of DDH in children. Study design Databases such as PubMed, Embase, Cochrane Library were searched, from inception to April, 2022, for studies applying 3D navigation-assisted osteotomy in DDH children. Methods There were 626 articles identified. According to the search strategy and inclusion criteria, 7 studies were finally included, with a total of 288 cases. Study screening, data extraction, and quality assessment were conducted by two reviewers independently. Data analyses were performed using RevMan 5.4 software. Results There were 7 retrospective cohort studies included. Meta-analysis showed that 3D navigation-assisted DDH osteotomy resulted in shorter duration of surgery [I2=88%, REM, MD=22.86, 95%CI (-27.29, -18.43), p＜0.00001], less radiation exposure during surgery [I2=53%, REM, MD=2.76, 95%CI (-3.15, -2.37), p＜0.00001], and less intraoperative bleeding [I2=94%, REM, MD=26.83, 95%CI (-39.24, -14.41), p＜0.0001], compared with conventional DDH osteotomy. There was a significant difference in the number of patients with McKay clinical function graded as poor between the two groups [I2=0%, FEM, RR=0.20, 95%CI (0.05, 0.74), p=0.02], whereas there were no significantly statistical differences in the corrected acetabular index angle, postoperative leg length discrepancy, and number of patients with Severin X-ray graded as poor between the two groups (p＞0.05). Conclusion 3D navigation-assisted pelvis and thighbone osteotomy for DDH children could shorten duration of surgery and reduce intraoperative bleeding and X-ray exposure, presenting definite therapeutic effect.